Green Commuting and Gasoline Taxes in the United States - J. Ignacio Gimenez-Nadal; José Alberto Molina (Institute of Labor Economics (IZA), 2019)
This paper analyzes how gasoline tax rates are related to the time workers in the United States spend commuting by private car, public transport, or with other physical modes of transport. Our identification strategy relies on both between-state differences and time variations in gasoline taxes. Using the American Time Use Surveys for the years 2003 to 2015, we find that higher gasoline tax rates are related with less time spent in commuting. Furthermore, higher gasoline taxes are related to a lower proportion of commuting by private car, and higher proportions of commuting by public transport and/or a physical mode of transport (e.g., walking, cycling). Our results highlight the importance of gasoline taxes (and prices) on the consumption of energy for personal transport, as higher gasoline taxes are related to a greater use of "green" modes of transport, showing that fuel taxes are important for good management of the environment.
Keywords: D1; Q4; R4; 330; commuting time; public transport; walking/cycling; gasoline taxes